Assessing the Reliability of Mobility Interpretation From a Multi-Isotope Hair Profile on a Traveling Individual - Hu, Lihai; Chartrand, Michelle M. G.; St-Jean, Gilles; Lopes, Madenn; Bataille, Clément P. (Frontiers in Ecology and Evolution, 2020)
Forensic practitioners, archeologists, and ecologists increasingly use hair isotope profiles and isotope databases and maps to reconstruct the life history of unidentified individuals. Relationships between hair isotope profiles with travel history have been primarily investigated through controlled laboratory experiments. However, those controlled studies do not reflect the complex life history of modern individuals who often travel between multiple locations over different periods. Here, we collect one bundle of hairs from a volunteer whose primary residence is in Ottawa (Canada) but who traveled to multiple destinations over a period of 18 months. Those travels include multi-week trips to distant locations and multi-day trips to more local areas. We use multi-isotope profiles on the individual’s hairs coupled with isotope databases across the world to reconstruct travel history at sub-monthly temporal resolution. We compare the isotopic interpretation of mobility with the recorded travel history. A prominent shift in δ2H values is interpreted as a westward movement towards central Canada, which corresponds to a month-long road-trip to the Prairie. We observed a marked negative excursion in δ13C values along the hairs profile, which was related to a multi-week-long trip to several countries in Europe. Except for an exceptionally variable interval likely driven by health issues, δ15N values show very little fluctuation across the entire profile, indicating consumption of consistent amounts of animal or marine-based protein at different locations. The isotopic shifts in the proximal part of the hair reveal a clearer picture of traveling destinations than the shifts in the distal part, which have larger uncertainty in terms of timing and amplitude. Except for the last couple of months before collection, 87Sr/86Sr ratios show little variation throughout the profile likely due to recent exchange with Ottawa tap water during bathing or showering. The different 87Sr/86Sr ratios in the month preceding collection appear to partially preserve the 87Sr/86Sr ratio of the volunteer’s diet. This study demonstrates the interest of using multi-isotope systems and large isotopic databases to reconstruct individual mobility. This study also underlines the challenges in linking isotope data to mobility, particularly in rapidly growing keratinous tissues.